La lettera di Bellarmino a Foscarini 400 anni dopo - Giostra, Alessandro (Alpha Omega, 2015)
Summary: Saint Robert Bellarmine’s letter to Paolo Antonio Foscarini concerns the relationship between biblical exegesis and Copernican astronomy in the early seventeenth century. It can be considered one of the most important documents on the interaction between science and faith in the entire history of thought. The four hundredth anniversary of this letter offers the opportunity to highlight its contents and to connect them with the condemnation of Galileo Galilei in 1633, following the issue of the Dialogue on the Two Chief World Systems. Bellarmine was much more than a Jesuit exegete and Consultor of the Holy Office, as in his youth he had been assigned to teach mathematics in some colleges run by his order. Thus, his expertise in both science and Scriptures rendered him able to deal with the intriguing question of their inter-relationship. Key words: St. Robert Bellarmine, Paolo Antonio Foscarini, Galileo Galilei, science and biblical exegesis, the Copernican question, the Roman College Parole chiave: San Roberto Bellarmino, Paolo Antonio Foscarini, Galileo Galilei, scienza ed esegesi biblica, questione copernicana, Collegio Romano.